Dynamic analysis of gene signatures in the progression of COPD. Issue 2 (6th March 2023) - Jiang, Junchao; Chen, Shengsong; Yu, Tao; Chang, Chenli; Liu, Jixiang; Ren, Xiaoxia; Niu, Hongtao; Huang, Ke; Li, Baicun; Wang, Chen; Yang, Ting
Aims: Oxidative stress is an important amplifying mechanism in COPD; however, it is unclear how oxidative stress changes and what its exact amplification mechanism is in the pathological process. We aimed to dynamically analyse the progression of COPD and further elucidate the characteristics of each developmental stage and unveil the underlying mechanisms. Methods: We performed a holistic analysis by integrating Gene Expression Omnibus microarray datasets related to smoking, emphysema and Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification based on the concept of gene, environment and time (GET). Gene ontology (GO), protein–protein interaction (PPI) networks and gene set enrichment analysis (GSEA) were used to explore the changing characteristics and potential mechanisms. Lentivirus was used to promote HIF3A overexpression. Results: In smokers versus nonsmokers, the GO term mainly enriched in "negative regulation of apoptotic process". In later transitions between stages, the main enriched terms were continuous progression of "oxidation-reduction process" and "cellular response to hydrogen peroxide". Logistic regression showed that these core differentially expressed genes (DEGs) had diagnostic accuracy in test (area under the curve (AUC)=0.828) and validation (AUC=0.750) sets. GSEA and PPI networks showed that one of the core DEGs, HIF3A, strongly interacted with the ubiquitin-mediated proteolysis pathway. Overexpression of HIF3A restored superoxide dismutase levels and alleviated the reactive oxygen species accumulation caused by cigarette smoke extract treatment. Conclusion: Oxidative stress was continuously intensified from mild emphysema to GOLD 4; thus, special attention should be paid to the identification of emphysema. Furthermore, the downregulated HIF3A may play an important role in the intensified oxidative stress in COPD. Oxidative stress is especially intensified from mild emphysema to GOLD 4 and downregulated HIF3A may contribute to this https://bit.ly/3FjUhQW